Y-REALITY AS A SHIFT FROM "GREAT MODERATION" TO "GLOBAL CHAOS": ASSESSMENT OF GLOBAL MACROECONOMIC AND CRISIS PROCESSES THROUGH THE PRISM OF GENERATIONAL DIALOGUE AND DEVELOPMENT ISSUES - Reznikova, Nataliia V.; Ptashchenko Оlena V.; Chugayev, Oleksii A.; Ivashchenko, Oksana A. (Journal of Strategic Economic Research, 2023)
The purpose of the article is to determine the features of the development of the world economy during the formation of the predominant role of Gen Y in the structure of the population, Y-reality is defined as a common historical context for generations that affects their economic behavior and predetermines challenges that limit the choice of consumption patterns, savings and other economic activity for Gen Y(millennial), the maturation process occurred during the Great moderation period, which lasted from mid-1980 until at least 2007. Great moderation was characterized by a low level of inflation, stable economic growth, the end of the "era" of uncertainty, an increase in the willingness to take risks, an increase in the prices of financial assets, and a decrease in the volatility of business cycle fluctuations in developed countries compared to previous decades. The period of Great Moderation ended with the onset of the global financial crisis of 2008–2009. The "New Norm" of the world economy or "Global Chaos" since 2008 has been characterized by eight trends: deterioration of US-China relations; aggravation of political fragmentation within the EU; further accumulation of debts and injection of artificial liquidity not into the financial, but into the real sector; inflation; increasing tax pressure on the rich as one of the tools to combat economic inequality; actualization of environmental topics, in particular, the climate issue with the prospect of introducing a carbon tax; technological revolution and technological confrontation, which will be determined by the coexistence of different technological standards; intensifying intergenerational competition with Gen Y predominating by 2030, which will set the global agenda and ultimately the demand for policy and how it is implemented. It is noted that in the conditions of the formation of the information and digital economy, Gen Y revised their approaches to employment, which is accompanied by the transformation of Gen Y human capital into network human capital. Y-reality is characterized by: the transition from efficiency to sustainability in strategic planning, which will affect the slowdown in productivity growth; increased demand from market agents for government participation; development of public-private partnership; increased deglobalization, which will accelerate the decline in productivity; rising unemployment; decrease in consumption; decrease in savings; an increase in debt; declining coordination of international economic policy. The impact of the coronavirus crisis on the economy (coronanomics) not only provokes a temporary drop in production, but also changes the basis for the functioning of the world economy, laying the foundations for sustainable economic imbalances. A specific feature of Y-reality is recognized as a change in approaches to monetary policy (quantitative easing and hedge money), as well as a human-centric quantitative easing known as "basic guaranteed income". Y-reality will be characterized by the search for new indicators of well-being and economic growth, in particular, which will lead to the realization of a new purpose of economic systems and the formation of a "new norm" of rational economic behavior, taking into account the impact of human activities on the environment. The slowdown in economic growth under Y-reality conditions becomes sustainable, it is objectively determined by the presence of numerous imbalances, and therefore it should be treated as a given. "Global disorder" came to mean not only the existing state of affairs and contradictory trends, but also the desired state, transforming the meaningful content of the concept of "crisis", giving it the connotation of a stage of the cycle, which can give impetus to development. The acronyms SPOD, VUCA and BANI were considered, which characterized the transformational processes in the modern economic system and the formation of Y-reality.